19.8k views
3 votes
Find derivative for 3x³ + 2xy + 4y²=0.

2 Answers

5 votes

Answer:


(dy)/(dx)= -(9x^2+2y)/(2(x+4y))

Explanation:

Find the derivative of
3x^3 + 2xy + 4y^2 = 0.

In order to find the derivative of this function,
(dy)/(dx), we can start by noticing that there are two variables in this problem, x and y.

Since we want the derivative with respect to x, every time we encounter the variable “y” in this problem we can change it to
(dy)/(dx). We will see this happen later on in the solving process by using implicit differentiation.

Let’s start by taking the derivative of the entire function:


  • (d)/(dx) (3x^3 + 2xy + 4y^2 = 0)

Using the Power Rule and the Product Rule, we can perform implicit differentiation on this equation. Let’s take the derivative of each separate piece in this function:


3x^3 \rightarrow 3(3x^3^-^1) \rightarrow 9x^2 Power Rule


2xy \rightarrow (2x * (dy)/(dx) + y * 2) Product Rule


4y^2 \rightarrow 2(4y) * (dy)/(dx) \rightarrow 8y * (dy)/(dx) Power Rule & Implicit Differentiation

Let’s combine these steps into one comprehensive operation:


  • 9x^2 + (2x * (dy)/(dx) + y * 2) + 8y * (dy)/(dx) = 0

Simplify.


  • 9x^2 + 2x(dy)/(dx) + 2y + 8y (dy)/(dx) = 0

Keep all terms containing
(dy)/(dx) on the left side of the equation and move everything else to the right side of the equation. This way we can solve for
(dy)/(dx), which, in this case, is the derivative of the original function.

Subtract
9x^2 and
2y from both sides of the equation.


  • 2x(dy)/(dx) +8y (dy)/(dx) = -9x^2-2y

Factor out dy/dx from the left side of the equation.


  • (dy)/(dx)(2x+8y) = -9x^2-2y

Divide both sides of the equation by (2x + 8y).


  • (dy)/(dx)= (-9x^2-2y)/(2x+8y)

You can leave it in this form, or you can convert this to either:


  • (dy)/(dx)= (-9x^2-2y)/(2(x+4y))

  • (dy)/(dx)= -(9x^2+2y)/(2(x+4y))
User Alex Nikolsky
by
4.4k points
2 votes

Answer:


y'=(-9x^2-2y)/(2(x+4y))

General Formulas and Concepts:

Algebra

  • Equality Properties

Calculus

  • Chain Rule:
    (d)/(dx)[f(g(x))] =f'(g(x)) \cdot g'(x)
  • Basic Power Rule: f’(x) = c·nxⁿ⁻¹
  • Derivative of a constant equals 0
  • Implicit Differentiation

Explanation:

Step 1: Define equation

3x³ + 2xy + 4y² = 0

Step 2: Find 1st Derivative

  1. Set up Derivative:
    (dy)/(dx) [3x^3 + 2xy + 4y^2 = 0]
  2. Take Implicit Differentiation:
    9x^2+(2y+2xy')+8yy'=0

Step 3: Find Derivative (Solve for y')

  1. Define:
    9x^2+(2y+2xy')+8yy'=0
  2. Move 9x² over:
    2y+2xy'+8yy'=-9x^2
  3. Move 2y over:
    2xy'+8yy'=-9x^2-2y
  4. Factor y':
    y'(2x+8y)=-9x^2-2y
  5. Isolate y':
    y'=(-9x^2-2y)/(2x+8y)
  6. Factor GCF:
    y'=(-9x^2-2y)/(2(x+4y))
User Thermz
by
4.6k points